[en] PERFORMANCE OF QAM QUATERNARY SYSTEMS IN NONLINEAR CHANNELS - ERNESTO LEITE PINTO (MAXWELL, 2007)
[pt] É feito um estudo comparativo de diversos sistemas de modulação digital QAM-4 propostos recentemente na literatura especializada, visando aplicações a canais não lineares. São estabelecidas e implementadas técnicas eficientes para estimação de parâmetros de desempenho destes sistemas, através da simulação em computador. São levantados diversos resultados de desempenho, que possibilitam uma verificação das potencialidades dos sistemas estudados para se reduzir a degradação de performance devido à(s) não linearidade(s) do canal, assim como uma indicação dos sistemas mais eficientes. === [en] Several 4-QM digital modulation systems recently proposed in the literature for application to nonlinear channels are studied and their performances are compared through computer simulation. Efficient techniques to estimate performance parameters from the simulated digital signals are developed and used for extensive computations of power spectrum and error probability degradation even in the presence of adjacent channel interference. The results provide an evaluation of the potential of some new techniques to improve performance in nonlinear channels and also an indication of the most efficient among these techniques.